Moderating Effect of Mindfulness on the Relationships Between Perceived Stress and Mental Health Outcomes Among Chinese Intensive Care Nurses - Lu, Fang; Xu, Yuanyuan; Yu, Yongju; Peng, Li; Wu, Tong; Wang, Tao; Liu, Botao; Xie, Junpeng; Xu, Song; Li, Min (Frontiers in Psychiatry, 2019)
This study aimed to explore the potential moderating effect of mindfulness and its facets in the relationships between perceived stress and mental health outcomes (burnout, depression, anxiety, subjective well-being) among Chinese intensive care nurses. A total of 500 Chinese intensive care nurses completed self-report measures of mindfulness, burnout syndromes, perceived stress, depression, anxiety and subjective well-being. Correlation and hierarchical multiple regressions were applied for data analysis. Mindfulness moderated the effects of perceived stress on emotional exhaustion (the core component of burnout syndrome), depression, anxiety, positive affect and negative affect, but not on the other two dimensions of burnout and life satisfaction. Further analyses indicated that the ability of acting with awareness was particularly crucial in improving the effects of perceived stress on depression. These results further broaden our understanding of the relationship between perceived stress and burnout, depression, anxiety, subjective well-being, by demonstrating that mindfulness may serve as a protective factor for alleviating or eliminating the negative effects of perceived stress on depression, anxiety and burnout syndrome and subjective well-being, and may instigate further research into targeted mindfulness interventions for Chinese intensive care nurses.